Substrate Shift Reveals Roles for Members of Bacterial Consortia in Degradation of Plant Cell Wall Polymers - Carlos, Camila; Fan, Huan; Currie, Cameron R. (Frontiers in Microbiology, 2018)
Deconstructing the intricate matrix of cellulose, hemicellulose and lignin poses a major challenge in biofuel production. In diverse environments in nature, some microbial communities, are able to overcome plant biomass recalcitrance. Identifying key degraders of each component of plant cell wall can help improve biological degradation of plant feedstock. Here, we sequenced the metagenome of lignocellulose-adapted microbial consortia sub-cultured on xylan and alkali lignin media. We observed a drastic shift on community composition after sub-culturing, independently of the original consortia. Proteobacteria relative abundance increased after growth in alkali lignin medium, while Bacteroidetes abundance increased after growth in xylan medium. At the genus level, Pseudomonas was more abundant in the communities growing on alkali lignin, Sphingobacterium in the communities growing on xylan and Cellulomonas abundance was the highest in the original microbial consortia. We also observed functional convergence of microbial communities after incubation in alkali lignin, due to an enrichment of genes involved in benzoate degradation and catechol ortho-cleavage pathways. Our results represent an important step towards the elucidation of key members of microbial communities on lignocellulose degradation and may aide the design of novel lignocellulolytic microbial consortia that are able to efficiently degrade plant cell wall polymers.